Hoard of thunder: Philippine short stories in English: 1990 to 2008 - Abad, Gemino H., editor (Quezon City: The University of the Philippines Press, 2012)
v.1. 1990 to 2000 - v.2. 2001 to 2008.
Includes bibliographical references.
Keywords: Short stories, Philippines (English).